A comparison of the effect of mindfulness and relaxation on responses to acute experimental pain. (21st November 2012) - Sharpe, L.; Nicholson Perry, K.; Rogers, P.; Refshauge, K.; Nicholas, M.K.
Abstract Background This study aimed to investigate the efficacy of mindfulness training in comparison with relaxation training on pain, threshold and tolerance during the cold pressor task. Methods Undergraduate psychology students (n = 140) were randomly assigned to receive reassuring or threatening information about the cold pressor. Participants were then re‐randomized to receive mindfulness or a control intervention: relaxation training. Results Analyses confirmed that the threat manipulation was effective in increasing worry, fear of harm and expectations of pain, and reducing coping efficacy. Interaction effects revealed that mindfulness was effective in increasing curiosity and reducing decentring under conditions of high threat but not low threat. Other interactions on cognitive variables (attentional bias to pain and self‐focus) confirmed that mindfulness and relaxation appeared to exert influences under different conditions (i.e. mindfulness: high threat; and relaxation: low threat). Despite these cognitive effects being discerned under different conditions, there were no differences between mindfulness and relaxation on pain, tolerance or threshold in either threat group. Conclusions These results show that a single, brief session of mindfulness based on body scanning is not sufficient to change the way in which individuals approach an experimental pain task in comparison with relaxation, which has previously been shown to be ineffective.